Принцип «рacta sunt servanda» у механізмі забезпечення виконання зобов’язань за міжнародними договорами - Киргізова, В. С.; Маринів, І. І. (НДІ ПЗІР НАПрН України, 2022)
Стаття висвітлює юридичний зміст та сутність принципу «pacta sunt servanda». Автор займає позицію, згідно з якою обов’язковість міжнародних договорів ґрунтується не лише на погоджувальній природі договірних норм, а й на взаємній зацікавленості сторін у договорі. У статті пояснюється природа принципу «pacta sunt servanda» з позиції «jus cogens», що теоретично обґрунтовує значення принципу, як передумови формування механізму забезпечення виконання зобов’язань за міжнародними договорами. Ґрунтуючись на низці філософсько-правових теорій, найпоширенішими з яких є теорія обіцянки, вольова теорія, а також теорія ефективності, «pacta sunt servanda», як один із принципів договірного права, є загальновизнаним у правовій науці. Вивчення цих теорійобґрунтувань дозволяє констатувати відсутність історичної наступності між початковим і наступними значеннями принципу, і, навіть, відсутність консенсусного погляду у доктрині. Крім того, різні підстави «pacta sunt servanda» мають різноспрямований і, часом, взаємовиключний характер. Нарешті, жодна з них, опираючись на загальні правові і філософські поняття, не має логічного зв’язку з правовою природою договору. За таких обставин цілком зрозумілою постає неоднозначність розуміння розглянутого принципу, як законодавцем, так і суб’єктом правозастосування. Усвідомивши необхідність дотримання законів, а також, як і дотримання міжнародних договорів, на рівні особистості, держава повинна усвідомити необхідність і неминучість багаторівневої взаємодії у міжнародній сфері. Тільки розуміння того, що в реалізації спільної волі та співробітництва можна досягти вирішення міжнародних проблем, які нині постали перед міжнародним співтовариством, прийняття можливості взаємодії для досягнення загального інтересу, а не задоволення поточних економічних потреб кожної держави окремо, дозволить вирішити багато глобальних проблем сучасності та вийти на новий рівень розуміння права, як інструмента побудови нової реальності в рамках взаємодії держав. У зв’язку з цим принцип «pacta sunt servanda» набуває дедалі більш глобальних масштабів. Керуючись ним і застосовуючи його до поточних і майбутніх реалій, усвідомлюючи його значимість та необхідність регулювання міжнародних відносин, можна говорити про побудову нового світового порядку, виходячи з вищих моральних цінностей права. Problem setting. The mechanism for ensuring the fulfillment of obligations under international treaties is a complex legal phenomenon that includes a number of international legal institutions (the institution of obligation, institutions related to good faith, means of ensuring the fulfillment of obligations, institutions of international judicial bodies, institution of responsibility). The main premise that contributed to the formation of the mentioned institutional mechanism is the principle «pacta sunt servanda» «agreements must be fulfilled», which concentrated in itself the idea of the binding nature of international agreements, and later the conscientiousness of their implementation. Denoting the binding nature of any legal agreement, the principle «pacta sunt servanda» is one of the main principles of contract law. However, its implementation is accompanied by a number of problems, the solution of which requires the development of an appropriate scientific basis. Analysis of recent researches and publications. The analysis of recent researches and publications shows that the issue of the principle of contractual law “pacta sunt servanda” has repeatedly attracted the attention of the scientific community. Some of its aspects were considered by both Ukrainian and foreign scientists, including: S. I. Afanasenko, D. P. Bogatchuk, O. V. Butkevich, S. V. Gonzalez Sinisterra, Z. M. Yudin and others. However, most of the research and publications available today are rather superficial in nature. Target of the research is to analyze the legal meaning and essence of the principle «pacta sunt servanda». Article’s main body. The purpose of the article is to analyze the legal meaning and essence of the principle «pacta sunt servanda». The article highlights the legal meaning and essence of the «pacta sunt servanda» principle. The author takes the position that the binding nature of international agreements is based not only on the consensual nature of contractual norms, but also on the mutual interest of the parties in the agreement. The article explains the nature of the principle «pacta sunt servanda» from the standpoint of «jus cogens», which theoretically substantiates the meaning of the principle as a prerequisite for the formation of a mechanism for ensuring the fulfillment of obligations under international treaties. Based on a number of philosophical and legal theories, the most common of which are the theory of promise, the will theory, as well as the theory of efficiency, «pacta sunt servanda», as one of the principles of contract law, is generally recognized in legal science. The study of these theories justifications allows us to ascertain the absence of historical continuity between the initial and subsequent meanings of the principle, and even the absence of a consensus view in the doctrine. Conclusions and prospects for the development. Realizing the need to observe laws, as well as observing international treaties, at the individual level, the state must realize the necessity and inevitability of multi-level interaction in the international sphere. Only the understanding that in the implementation of the common will and cooperation it is possible to achieve a solution to the international problems that are currently faced by the international community, accepting the possibility of interaction to achieve the common interest, and not to meet the current economic needs of each state separately, will allow solving many global problems of our time and leaving to a new level of understanding of law as a tool for building a new reality within the framework of the interaction of states. In this regard, the principle of «pacta sunt servanda» is gaining more and more global scope.
Keywords: pacta sunt servanda; jus cogens; міжнародні договори; зобов’язання держава; забезпечення зобов’язань; pacta sunt servanda; jus cogens; international treaties; obligations of the state; security of obligations